141k views
4 votes
Simplify m2b4r3/r4b4m

User Busti
by
4.5k points

1 Answer

6 votes

We have to simplify the next given expression:


(m^2b^4r^3)/(r^4b^4m)

First, we can cancel the common terms b⁴/b⁴ = 1

Then:


(m^2r^3)/(r^4m)

Now, we need to use the next exponents property:


(a^m)/(a^n)=a^(m-n)

For m:


(m^2)/(m)=m^(2-1)=m

Therefore:


(mr^3)/(r^4)

For r:


(r^3)/(r^4)=r^(3-4)=r^(-1)

Use for r the next exponent property:


a^(-m)=(1)/(a^m)

Hence, we have the next simplified expression:


m\cdot(1)/(r)
=(m)/(r)

User Justin Simon
by
5.0k points